AN ANALYSIS MORAL VALUE IN NIKOLAI GOGOL OF THE SHORT STORY “THE OVERCOAT” - Martina Girsang; Rinny Sherina Putri Sianturi; Yance Sihotang; Nelly Kristin; Arta Jelita Sitohang (Asosiasi dosen IDEBAHASA KEPRI, 2023)
In this study, the researcher chose the short story of Nikolai Gogol “The Overcoat”. The short story to be analyzed the importance of moral values used theory of Nurgiantoro (1995:324). The formulation of problem in this research is “ What are the moral values as reflected in the short story “The Overcoat”. The research method of this study is descriptive qualitative method. The primary data is text from the short story “The Overcoat”. The secondary data is taken from many literary books and some relevant materials to support and complete the primary data sources. The result of this study is there are some moral values in the short story” The Overcoat”. They are forms of moral values ​​in God, form of moral values in human life with itself, and form of moral values in the social life.